Perda de produtividade na cultura do milho (Zea mays) pela competição de diferentes densidades de capim amargoso (Digitaria Insularis) - Bazanella, Renan Henrique de Oliveira (2021)
One of the factors that affect corn yield is the presence of weeds in the cultivated areas. This presence has a direct influence on the production system, generating competition for soil and environmental resources with the crop of interest. Sourgrass, being a monocotyledonous weed and presenting resistance to glyphosate, makes it management difficult to obtain satisfactory control. The presence of this weed in commercial corn crops generates a high degree of competition with the crop, which can be enhanced according to its population density, negatively impacting the profitability of the production system. In this sense, this work aimed to evaluate the loss of productivity caused by the corn crop in competition with different densities of bitter grass. The work was conducted at the premises of the Universidade Tecnológica Federal do Paraná, Campus Dois Vizinhos. The completely randomized design was used, with four treatments (densities of bitter grass) and one control, with four replications. The densities of bitter grass were 1, 2, 4, and 6 plants / m² with free control of bitter grass plants, 0 plants / m2.Data were collected at 123 days after corn emergence (DAE), before harvest, where the following variables were evaluated: plant height and ear insertion height. After harvesting the grains, the material was taken to the laboratory to carry out a partial productivity survey / per plot and productivity per hectare. Through the obtained data itwas concluded that the productivity of the corn decreased as the density of bitter grass / m² increased. For the variable plant height and ear insertion height, a decrease was noted as the density of bitter grass / m² increased. In terms of productivity, competition between bitter grass and corn reduced corn productivity by up to 18.93% (1.800 kgha-1).